Parametric stochastic instability of connected oscillator - Buts, V.A.; Kovalchuk, I.K. (Вопросы атомной науки и техники, 2003)
Oscillators are used for investigation different physical processes, for example, oscillation in plasma, modeling of continuous medium ets. The large interest is fluctuation influence on oscillation processes. It is well known that multiplicative fluctuation causes the instability in thus systems. We investigated the systems of two and three connected oscillators. We have shown that it is possible considerably to increase the increment of this instability. The conditions when this is possible are obtained. The numerical simulation of processes in the system of two and three connected oscillators was carried out. Oscillation increment was increasing when correspond conditions were performed.